Stock assessment of threadfin breams (Nemipterus spp.) of India - Murty, V Sriramachandra; Rao, T Appa; Srinath, M; Vivekanandan, E; Somasekharan Nair, K V; Chakraborty, S K; Raje, S G; Zacharia, P U (Indian Journal of Fisheries, 2011)
The annual average estimated landing of threadfin bieami in India during 1980-83 was 22 247 tonneswhich increased to 48100 tonnes during 1984-88;amaxinium of about 60 000 tonnes landed in 1986. Over90% of threadfin bream catch in the coumiy was obtained by commercial trawlers. Among the maritimestates of fodia, Kerala contributed maximum (52%) to the nemipterid landings, followed by Maharashtra(13.6%), Tamil Nadu and Pondicheny (11.2%), Kamataka andGoa (8.8%), Gujarat (7.8%), AndhraPradesh(S.S%) and Oristn (1.1%). Though a total of six nemipterid species contributed to the fishety in differentstates, only two species viz Nemipterus japoiucus and N. mesoprion contributed significantly; the fomierwu most abundant in Tamil Nadu - POndicheny, Kamataka - Goa, Maharashtra and Gujarat and the latterin Andhra and Kerala. Periods of peak abundance were Januaiy-March in Andhra Pradesh, Kamataka-Goa,and Gujarat whereas Apiil-June in Maharashtra and July-September in Tamil Nadu - Pondicheny andKerala. The parameters of growth and mortality were estimated. The results of stock assessment from eachstate show that though there is scope to increase the effort by 40%-100% to get MSY from the fishinggrounds, the increase in yield will be marginal (1 %-12%). There is need to increase the cod end mesh sizeof uawl net (or length at first capture Lc) by 10-30% to get MSY. The maximimi possible yidd ofN.japonicus and N. mesoprion from the fishing grounds along east coast (Andhra Pradesh, Tamil Nadu andPondicherry) is around S 000 tonnes and along west coast between 43 000 tonnes and 46 000 tonnes. Theseare dose to the yidds in 1984-88. The problems in stock assessment and different options for managementof fisheries are discussed.